The Effects of Training and Work Placement on Employee Performance at PT Samator Gas Industri Cilegon Branch - Suhendi, Didi; Aprilliadi, Teddy; Dzikri, Ahlu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the effect of training and work placement on employee performance at PT Samator Gas Industri Cilegon Branch. The method used was quantitative with a multiple linear regression approach, involving 36 employees as a sample. The regression results showed that training had a significant effect on employee performance with a regression coefficient of 0.506 and a significance value of 0.000, which means that better training can improve employee performance. Meanwhile, job placement also has a significant influence on employee performance with a regression coefficient of 0.329 and a significance value of 0.000. The results of the simultaneous test (F Test) showed an F value of 45.665 with a significance value of 0.000, which means that the two independent variables, namely training and work placement, had a simultaneous significant effect on employee performance. With an R Square of 0.735, the model was able to explain about 73.5% of the variation in employee performance, while the remaining 26.5% was influenced by other factors that were not studied. Based on these results, it is recommended that companies improve training and job placement programs to match employees' skills and needs to improve their performance